An assessment of the significance of sacred forest status in maintaining forest condition and integrity - Rajak, Sauleha (Rhodes University, 2026)
Many sacred natural sites (SNS), including sacred forests (SFs), play an important role in biological conservation because religious beliefs associated with these sites have been instrumental in the protection of rare and endangered species, habitats and ecosystem services. Sacred natural sites are protected based on customary laws, e.g., restricted access and use, and codes of conduct. Sacred natural sites also conserve the cultural and spiritual identities and heritage of local communities as they are considered places of symbolic manifestations of cultural beliefs and traditions, and often contain cultural products or resources from which cultural artifacts are created. These sites allude to the important relationship locals share with nature in the belief of the divine or sacred in nature where deities or ancestral spirits reside, and where healing is found. In this way, SNS preserve community cultural values, heritage and history as part of the cultural landscape and serve as historical archives. Although some SNS form part of and are respected by local communities, and many have existed for long periods, SNS are not primarily conservation areas. Instead, SNS exist to fulfil sociocultural and spiritual needs within communities. As such, some SNS are not necessarily undisturbed and the traditional institutions managing these sites are not fixed entities. Indeed, SNS and the communities that govern and use them have been subjected to political, socioeconomic and cultural influences. Consequently, some SNS face serious threats and many have even disappeared. In some instances, they continue to offer opportunities for biodiversity conservation. Although the significance of some of these sites are often undervalued and overlooked by the state, conservation agencies, policies and laws, there has been a renewed interest in SNS as Other Effective Area-Based Conservation Measures (OECMs) for their successful preservation of both nature and culture. This study aimed to determine whether two SFs serve as a tool for promoting biodiversity conservation whilst underpinning the integrity of local cultural heritage. Therefore, the study examines the cultural identities of local communities, their beliefs, practices, and customs for the conservation of the biological diversity of the SFs. The study adopted a biocultural approach to examine the role of traditional ecological knowledge (TEK), traditional cultural beliefs and values, and indigenous institutions in relation to the integrity and condition of two SFs in Mazizini and Mabasa, in KwaZulu-Natal. Given South Africa's political history, the biocultural approach is relevant in understanding the direct and indirect drivers of change that have altered human behaviour, cultural and spiritual values and beliefs of the sacred in nature and allows assessment of the consequences of these changes. A biocultural framing recognises place-based relationships and enduring social-ecological systems that are based on local priorities, indigenous knowledge and traditional methods to address biological and cultural diversity concerns parallel to the dynamic nature of culture, and how natural resources are used and conserved. The biocultural approach allows an understanding of the position local communities play in their agency towards conserving nature as custodians of their spiritual landscapes. Thus, the approach offers an opportunity to understand the link between the importance of indigenous people, their TEK and their ancestral manifestations in nature in stewarding biodiversity. This study sought to recognise and include biocultural heritage and biophysical components that are interdependent in social-ecological systems, as a unique form of OECM. To examine cultural and social-ecological relationships with SFs and how these relationships impact their integrity, quantitative and qualitative methods were employed. Quantitative methods included ecological field surveys and time-series analysis (of repeat measurements of spectral, temporal and spatial data) using Geographical Information System and remote sensing to determine the current ecological condition and integrity of the SFs and how it has changed over the recent past. Qualitative methods included key informant interviews, participatory rural appraisal techniques, oral histories, document analysis and scenario workshops to understand local perceptions and values of the SFs, the role of the community in preserving the SFs, complex causalities and change trajectories of the biocultural systems, i.e., integrated systems of cultural heritage and biological diversity that interact with one another, and emerging pathways by making sense of the future. Given the mixed-methodological approach and the study’s interdisciplinary nature, triangulation across methods and findings was applied to better understand the belief in ancestral ‘power’, the significance of traditional authorities, the legacy of traditional cultural practices, anthropogenic influences, ecological condition and ecosystem services. Over the last three centuries, many indigenous communities have experienced various changes broadly related to imperialism, modernisation, institutionalised religions and globalisation which include demographic changes and the erosion of traditional beliefs that have threatened or destroyed many SFs. Some communities are still able to retain their indigenous beliefs and cultural heritage which serve as effective controls in protecting SFs. This study found that the communities of Mabasa and Mazizini have become fragmented within the broader South African political and socioeconomic context. Via the qualitative methods, various historical, and socio-political forces were identified as impinging on the cultural beliefs, values and practices of the local communities. This has undermined the very foundation of the integrity of the sacredness of the forest, particularly in Mabasa which was greatly influenced by missionary practices introduced in the 1920s. Through the in-depth qualitative analysis, the influences of the different political eras these communities have experienced over decades were considered, including the local indigenous history. The Colonial era appears to have had a significant impact on local Zulu belief in the veneration of ancestors, whereas the relevance of traditional governance was systematically undermined during the Apartheid era. Both of these have contributed to the decline in cultural practices and values associated with the SFs, compromising the traditional and ‘spiritual’ custodianship of the forests. These have been further exacerbated by some unintended consequences of ideologies and policies adopted by the elected democratic government in 1994. The physical landscape difference between the two sites plays a role in this dynamic. The SF, known as the Hlathi lama Khosi, is located on the sacred mountain in Mazizini, where its sacred significance is maintained through taboos and restricted access to the SF. However, sociopolitical changes over the years have undermined the biocultural integrity of the community’s relationship with the site, as evident by the exploitative use of the culturally significant Nhlankomo forest, which is also meant to be restricted from access and use. Despite the restrictions placed on both forests, permission was given to survey the Nhlankomo forest, whilst the Hlathi lama Khosi remained restricted to only the royal family. The quantitative data indicated that the ecological integrity of the sacred Funjwa forest in Mabasa and the culturally significant Nhlankomo forest were not significantly different as compared to adjacent non-sacred forests, whilst the restricted access to the Hlathi lama Khosi, due to the practice of customary secrecy, has made its ecological condition impossible to assess. Both SFs revealed a high biological diversity and display population stability, but this may be threatened if unsustainable practices and levels of harvesting are not curbed, given that some of the already endangered or vulnerable species are under threat. Resource acquisition changes, the influence of mainstream Western religions has increased fundamentalism and religious conversion, the loss of TEK and youth apathy towards nature illustrate how biocultural relations within communities have affected. It is, therefore, vital to understand local perceptions and values of nature, changes in environmental strategies, and the role of the community in preserving the biological diversity of SFs. The results from this study will be useful to local authorities to develop specific forest management strategies for OECMs, which requires a plural approach to the conservation of SFs that incorporates multiple values. While the methodology used in this study may not be conducive to supporting all national and subnational forest monitoring systems, it provides valuable insights into incorporating diverse, multi-dimensional perspectives spanning the natural, human and spiritual, that can assist in developing context-specific conservation strategies. Lastly, given that the approach adopted in this study is not yet widely recognised, this study provides insights into how the interrelationships between ecological and cultural diversity at the local level can be approached. The inclusion of various stakeholders and the merit of scenario workshops helped the gaps between the different constituencies and has provided the space to develop agreed upon longer-term plans for the SFs.
a biocultural perspective
Keywords: Uncatalogued